Analysis of Association between Morphometric Parameters of Growth Plate and Bone Growth of Tibia in Mice and Humans. (December 2021) - Wilson, Kimberly; Usami, Yu; Hogarth, Danielle; Scheiber, Amanda L.; Tian, Hongying; Oichi, Takeshi; Wei, Yulong; Qin, Ling; Otsuru, Satoru; Toyosawa, Satoru; Iwamoto, Masahiro; Abzug, Joshua M.; et al.
Objective: The purposes of this study are to evaluate which growth plate parameters are associated with bone growth in mice and to compare the mouse results with those in humans. Design: The sagittal sections of the proximal growth plate of the mouse tibia from neonate to young adult stages were subjected to histomorphometric and functional analyses. The radiographic images of tibias of human patients until puberty were analyzed to obtain the tibia length and the proximal growth plate height. It was found that a linear correlation best modeled the relationship between the growth plate variables with the tibia growth rate and length. Results: In mice, total height, resting zone height, combined height of the proliferation and prehypertrophic zones, proliferation activity, and the total width of tibia growth plate showed high linear correlation with tibia bone length and bone growth rate, but the hypertrophic zone height and the growth plate area did not. In both mice and humans, the total growth plate width of tibia was found to have the strongest correlation with tibia length and growth rate. Conclusions: The results validated that growth plate total height, the height of the resting zone and cell proliferation activity are appropriate parameters to evaluate the balance between growth plate activity and bone growth in mice, consistent with previous reports. The study also provided a new growth plate parameter candidate, growth plate width for growth plate activity evaluation in both mouse and human tibia bone.